Competitiveness in Bulgaria : An Assessment of the Real Effective Exchange Rate - Sorsa, Piritta (IMF Working Papers; Working Paper ;, 2004)
This paper presents an empirical analysis of the medium- and long-term determinants of the real (effective) exchange rate (RER) of the Bulgarian lev using elements from the natural real exchange rate (NATREX) and the behavioral equilibrium exchange rate (BEER) approaches. The results indicate that the RER is driven by fundamentals, including labor productivity, terms of trade, world real interest rates, gross savings, and foreign direct investment. The model also shows that there is no significant misalignment of the Bulgarian lev.